Pro-Drop in Hijazi Arabic: A Minimalist Perspective - Issa AlQurashi (European Scientific Journal, ESJ, 2023)
This paper focuses on investigating the null subjects in Hijazi Arabic and addresses how they are derived and interpreted. There is a strong connection between rich verbal agreement inflection and pro-drop in HA due to the language's highly inflectional nature.  It is shown in this paper that HA is a consistent null subject language. This study is framed within Holmberg's (2005, 2010) theory of null subjects. Holmberg proposed that null subjects (henceforth NSs) are defective subject pronouns labeled Ps. The null subjects are derived via incorporation into T after the features valuation and union take place. The head T (a probe) has unvalued -features which are valued by the defective subject pronoun (a goal) and in return, the [u case] feature on P is valued by T. The incorporation of P into T forms a chain which is subject to chain reduction where the lower chain copy (the defective subject pronoun in spec-VP) receives a null spell out. The pronounced elements consist of the valued φ-features of T, which manifest as a verbal affix on the finite verb subsequent to the verb's incorporation into T. This reflects the deletion of the subject in spec-VP. The null subject is interpreted as a definite 3rd person null subject when the [uD(efiniteness)] feature of P is valued by an A-Topic (antecedent) in spec-TopP. On the other hand, it is interpreted as a definite 1st or 2nd person null subject if it is valued by speaker/addressee features in the domain of C (Complementizer).